Adverse Events Reporting of Clinical Trials in Exercise Oncology Research (ADVANCE): Protocol for a Scoping Review - Luo, Hao; Schumacher, Oliver; Galvão, Daniel A.; Newton, Robert U.; Taaffe, Dennis R. (Frontiers in Oncology, 2022)
Introduction Adequate, transparent, and consistent reporting of adverse events (AEs) in exercise oncology trials is critical to assess the safety of exercise interventions for people following a cancer diagnosis. However, there is little understanding of how AEs are reported in exercise oncology trials. Thus, we propose to conduct a scoping review to summarise and evaluate current practice of reporting of AEs in published exercise oncology trials with further exploration of factors associated with inadequate reporting of AEs. The study findings will serve to inform the need for future research on standardisation of the definition, collection, and reporting of AEs for exercise oncology research. Materials and methods The ADVANCE (ADverse eVents reporting of clinicAl trials iN exerCise oncology rEsearch) study will be conducted and reported following the PRISMA extension for scoping reviews guideline. Any type of clinical trial involving an exercise intervention in people living with and beyond cancer with a full-text report in English will be included. Six electronic databases (Embase, PubMed, Google Scholar, Web of Science Core Collection, SPORTDiscus, and CINAHL Plus) will be searched for studies. Two independent review authors will assess eligibility of identified studies, chart data using pre-established extraction forms, and evaluate adequacy of reporting of AEs-related data against a 20-item scoring checklist derived from the CONSORT (Consolidated Standards of Reporting Trials) harms extension. We will summarise results using descriptive and inferential analysis methods. Ethics and dissemination No ethics approval will be required to conduct the ADVANCE study owing to inclusion of only published data. The study results will be disseminated via publications in peer-reviewed journals and presentations at national and international conferences. Registration Open Science Framework: https://osf.io/NXEJD/ (doi:10.17605/OSF.IO/NXEJD).